THE BEBBINGTON QUADRILATERAL AND THE WORK OF THE HOLY SPIRIT. - Kidd, Thomas S. (Fides et historia, 2015)
The article discusses the Bebbington quadrilateral and the controversy over the important role played by the Holy Spirit in evangelical Christianity since its advent in the 1730s and 1740s. It cites the opposition of anti-charismatic pastor John MacArthur to the evangelicals' focus on the Holy Spirit. It provides a background of the ministry of U.S. missionary and evangelist George Whitefield in England and Wales in 1739. Several disagreements over the Holy Spirit's ministry are also examined.